“Tick a box: Yes □ No □ Maybe □” — How Can Intimacy Be Negotiated Consensually? (KULT_online, 2022)
While consent has become a widely recognized concept to distinguish between mutually negotiated or abusively coerced sexual practices, there is no consensus on what exactly it entails and how it can be realized or taught in sex education. The reviewed book sheds some light on those questions by turning to art and pedagogy as spaces to reflect on the nuanced gray areas of consent. Its sophisticated terminological clarifications, historical backgrounds and film analyses are followed by didactical manuals suggesting how the topic can be creatively implemented in curricula.